The 2003 Cricket World Cup : implications for identity formation and democratization prospects for Zimbabwe - Van der Merwe, Justin Daniel Sean (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2004.